Binding and Release of FeIII Complexes from Glucan Particles for the Delivery of T1 MRI Contrast Agents. (14th April 2020) - Patel, Akanksha; Asik, Didar; Snyder, Eric M.; Dilillo, Alexandra E.; Cullen, Paul J.; Morrow, Janet R.
Abstract: Yeast‐derived β‐glucan particles (GPs) are a class of microcarriers under development for the delivery of drugs and imaging agents to immune‐system cells for theranostic approaches. However, the encapsulation of hydrophilic imaging agents in the porous GPs is challenging. Here, we show that the unique coordination chemistry of Fe III ‐based macrocyclic T 1 MRI contrast agents permits facile encapsulation in GPs. Remarkably, GPs labeled with the simple Fe III complexes are stable under physiologically relevant conditions, despite the absence of amphiphilic groups. In contrast to the free Fe III coordination complex, the labeled Fe III ‐GPs have lowered T 1 relaxivity and act as a silenced form of the contrast agent. Addition of a fluorescent tag to the Fe III complex produces a bimodal agent to further enable tracking of the nanoparticles and to monitor release. Treatment of the iron‐labeled GPs with a maltol chelator or with mildly acidic conditions releases the intact iron complex and restores enhanced T 1 relaxation of the water protons. Abstract : Capture and release : Members of a new class of cationic Fe III ‐based MRI contrast agents can be encapsulated in yeast‐derived β‐glucan particles (GPs) in a stable form, despite GPs' porosity. Release of the contrast agents produces increased T 1 proton relaxation as triggered by mild acid or a bidentate chelator.